Role of the Enterprise Corporate Culture in Concepts of Organisational Changes - Otenko Irina Pavlovna; Chepelyuk Margaryta I. (Bìznes Inform, 2013)
The article analyses the “corporate culture” notion, which is an efficient instrument in the sphere of management of human resources, which influences enterprise competitiveness and factually is a must for high-quality and effective conduct of business. Corporate culture is “reduction” of the most important provisions of activity of the organisation, which identify its mission and development strategy, find their expression in a combination of social norms and values shared by majority of the employees. Corporate culture, as an indicator, characterises the level of development and operation of the organisation, since it influences, first of all, the socio-psychological climate, which sets the emotional background for activity of the whole personnel. Study of the role of corporate culture in concepts of organisational changes would allow using it as a factor of overcoming resistance of the personnel when realising changes and carrying out socio-psychological provision of managerial processes. In this event the organisation functions as an integral body and acts harmoniously to achieve the set goals.